Islamic Value-Based Reward and Punishment System Implementation in Enhancing Work Motivation in an Islamic Educational Foundation - Muhtar Gojali; Hasan Mud'is; Muhammad Hilmy Ibnu Muqti (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2026)
This study aims to describe the implementation of a reward and punishment system and its implications for employee work motivation at the Ar-Rifqi Educational Foundation, Bandung City, from the perspective of Islamic Education Management. Employing a qualitative case study design, data were collected through semi-structured interviews, participatory observation, and documentation involving foundation leaders, school unit heads, teachers, and educational staff (n = 13). Data analysis followed the interactive model data condensation, display, and conclusion drawing supported by source and technique triangulation. Findings reveal that the reward and punishment system is implemented gradually, transparently, and grounded in Islamic values such as justice (al-'adl), trustworthiness (amanah), and ethical conduct (adab). Rewards are provided in financial and non-financial forms, while punishments are applied through persuasive and educational approaches. The system contributes to improving employee discipline, responsibility, and work motivation (lateness decreased 68%, perfect attendance increased 83%, work motivation survey increased 28%). Communicative leadership and a religious work culture support implementation, whereas budget constraints and subjective performance assessment act as inhibiting factors. The study confirms that a reward and punishment system grounded in Islamic values can foster a professional and humanistic work culture in Islamic educational institutions.